Maxillary Antrolith: A Rare Cause of the Recurrent Sinusitis - Vijendra Shenoy; Vinod Maller; Vijetha Maller (Case Reports in Otolaryngology)
Introduction. An antrolith is a calcified mass within the maxillary sinus. The origin of the nidus of calcification may be extrinsic (foreign body in sinus) or intrinsic (stagnant mucus and fungal ball). Most antroliths are small and asymptomatic. Larger ones may present as sinusitis with symptoms like pain and discharge. Case Report. We report a case of a 47-year-old lady who presented with heaviness on the left side of the face and loosening of the left 2nd molar tooth since two months. CT scan of the osteomeatal complex and paranasal sinuses showed an opacification of bilateral maxillary sinus and an amorphous area of bone density in the left maxillary sinus. Because of the size of the mass, benign neoplasms were considered in the differential diagnosis. During an endoscopic sinus surgery, it was found to be an antrolith, which was successfully managed by antrostomy and Caldwell-Luc Surgery. Discussion. Antrolith is a rare condition. Rhinoliths are known to invade into the maxillary antrum, but a localised lesion in the antrum is very unusual. A case of an isolated antrolith is presented for its rarity and for differential diagnosis of localised antral disease. Conclusion. Antrolith should be considered as differential diagnosis of unilateral radio-opaque paranasal sinus lesions.